3D printing technology in healthcare: applications, regulatory understanding, IP repository and clinical trial status. (7th February 2022) - Kumar Gupta, Dipak; Ali, Mohd Humair; Ali, Asad; Jain, Pooja; Anwer, Md. Khalid; Iqbal, Zeenat; Mirza, Mohd. Aamir
Abstract: Mass consumerization of three-dimensional (3D) printing innovation has revolutionised admittance of 3D-printing in an expansive scope of ventures. When utilised predominantly for industrial manufacturing, 3D-printing strategies have rapidly attained acquaintance in different parts of health care industry. 3D-printing is a moderately new technology that has discovered promising applications in the medication conveyance and clinical areas. This review intends to explore different parts of 3D- printing innovation concerning pharmaceutical and clinical applications. Review on pharmaceutical products like tablets, caplets, films, polypills, microdots, biodegradable patches, medical devices (uterine and subcutaneous), patient specific implants, cardiovascular stents, etc. and prosthetics/anatomical structures, surgical models, organs and tissues created utilising 3D-printing is being presented. In addition, the regulatory understanding and current IP and clinical trial status pertaining to 3D fabricated products/medical applications have also been funnelled, garnering information from different web portals of regulatory agencies and databases. It is additionally certain that for such new innovations, there would be difficulties and questions before these are acknowledged as protected and viable. The circumstance demands purposeful and wary endeavours to acquire regulations which would at last prompt the accomplishment of this progressive innovation, thus various regulatory challenges faced have been conscientiously discussed.